The Effect of Storytelling with Audiovisual Books on Children's Anxiety Levels During Hospitalization - M. Fauzan Razuli; Yunike; Jawiah (CV. CENDIKIA JENIUS INDONESIA, 2024)
Background: Children with typhoid fever who undergo treatment in the hospital (hospitalization) tend to experience stress due to changes in the environment and health status they experience which will risk disrupting the healing process. The role of nurses in providing nursing care has a role in controlling this anxiety by providing diversion activities with audio-visual storybook media.The purpose of the diversion activity is to shift the focus of children who previously felt anxious due to the situation in the hospital to be reduced due to a diversion activity with audio-visual storybook media that makes children more happy and entertained. Methods: This research is a case study research using a descriptive design with a nursing care process approach consisting of assessment, nursing diagnoses, nursing interventions, nursing evaluation, and nursing documentation. Case study subjects in this study were 2 cases of Typhoid Fever with Anxiety nursing problems at Siti Fatimah Hospital, South Sumatra Province in 2024. Results: the results of the case study after the implementation of nursing to reduce anxiety levels in children with typhoid fever with audio-visual storybook media showed the results of patient 1 and patient 2 found that the level of anxiety decreased. As for what is obtained, there is a significant relationship between Anxiety and the provision of diversion activities with audio storybook media in children with Typhoid Fever. Conclusion : Nursing implementation to reduce anxiety levels in children with typhoid fever with audio-visual storybook media with Anxiety problems can be applied because it is effective for reducing anxiety in children.